STEEL-SLAG AS SUBSTITUTE TO NATURAL AGGREGATES, PROPERTIES AND THE INTERFACIAL TRANSITION ZONE - Lie, Han Ay (Diponegoro University, 2009)
Steel-slag is a residual product of the steel industry that has potential ability to pollute the ground water and soil containing heavy metals. To overcome this problem, attempts have been made for using the slag as substitute for both coarse and fine aggregates in concrete. The solidification process will prevent the metal components from polluting the water and soil. Test results on the mechanical properties of slag-concrete showed that while the compression strength of slag-concrete increased significantly as a function of slag-to-natural aggregate’s use, the tensile strength dropped accordingly. The substitution of fine-slag to Muntilan sand was even more negative, the compression strength decreased as a function of slag use. Research into the influences of the Interfacial Transition Zone was conducted, since the ITZ itself forms a weak link within the concrete matrix. The SEM tests were performed at the Quarter Laboratory, Department of Geology in Bandung using a Scanning Electron Microscope type JEOL.